1996
DOI: 10.1002/(sici)1098-2337(1996)22:5<357::aid-ab4>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid stimulatory effects of testosterone upon myotubule metabolism and sugar transport, as assessed by silicon microphysiometry

Abstract: A considerable number of studies have revealed behavioral circumstances that give rise to small or transient differences in circulating testosterone concentrations; however, careful consideration of androgen physiology leads to the disquieting conclusion that these differences are often unlikely to have much physiologic or behavioral significance. In the present report, we observe that small transients of testosterone secretion could have very rapid anabolic effects on a cultured muscle‐derived cell line. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 24 publications
(21 reference statements)
2
35
0
Order By: Relevance
“…We do not know whether egg treatment caused differences in circulating hormone levels in the nestlings, but higher blood levels of testosterone or related steroids may result in higher metabolic rates as has been found in adult birds and fishes (Buchanan et al 2001;Ros et al 2004). Moreover, testosterone is also known to increase anabolic processes at the cellular level ( Tsai & Sapolsky 1996).…”
Section: Discussionmentioning
confidence: 98%
“…We do not know whether egg treatment caused differences in circulating hormone levels in the nestlings, but higher blood levels of testosterone or related steroids may result in higher metabolic rates as has been found in adult birds and fishes (Buchanan et al 2001;Ros et al 2004). Moreover, testosterone is also known to increase anabolic processes at the cellular level ( Tsai & Sapolsky 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Sapolsky (1987) has provided another plausible explanation. T induces rapid increases in muscle anabolism (Tsai & Sapolsky, 1996) and lowers the threshold for dominance-related aggression mediated by structures of the "emotional brain" (LeDoux, 1996) such as the septum and the amygdala (Albert, Jonik, & Walsh, 1992). According to Sapolsky, increases in physical strength and aggressiveness associated with high rank or victory make an individual more physically fit and motivated to attain or retain high social rank.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dabbs and his collaborators reported that in female prison inmates, those with a more extensive record of aggressive behavior are higher in T (Dabbs & Hargrove, 1997) and that among adolescents, high-T girls are just as prone as high-T boys to engage in antisocial, rebellious behavior (Banks & Dabbs, 1996). Moreover, in a carefully designed double-blind study, van Honk et al (2001) showed that women treated with T showed a stronger cardiovascular response than women treated with placebo to perceived facial expressions of anger-a dominance signal (cf. Knutson, 1996)but not to happy or neutral faces.…”
Section: T-response Hypothesismentioning
confidence: 99%
“…Indeed, Tsai and Sapolsky (1996) proposed that short-term changes in testosterone levels, such as those observed in competition, may involve energy mobilization in muscle cells. They reported a 25% increase in metabolic rate in muscle cells in vitro within 1 min of exposure to testosterone.…”
Section: Libidomentioning
confidence: 90%